Factors associated with incomplete immunisation in children aged 12–23 months at subnational level, Nigeria: a cross-sectional study. Issue 6 (25th June 2021) - Eze, Paul; Agu, Ujunwa Justina; Aniebo, Chioma Lynda; Agu, Sergius Alex; Lawani, Lucky Osaheni; Acharya, Yubraj
Abstract : Objectives: National immunisation coverage rate masks subnational immunisation coverage gaps at the state and local district levels. The objective of the current study was to determine the sociodemographic factors associated with incomplete immunisation in children at a sub-national level. Design: Cross-sectional study using the WHO sampling method (2018 Reference Manual). Setting: Fifty randomly selected clusters (wards) in four districts (two urban and two rural) in Enugu state, Nigeria. Participants: 1254 mothers of children aged 12–23 months in July 2020. Primary and secondary outcome measures: Fully immunised children and not fully immunised children. Results: Full immunisation coverage (FIC) rate in Enugu state was 78.9% (95% CI 76.5% to 81.1%). However, stark difference exists in FIC rate in urban versus rural districts. Only 55.5% of children in rural communities are fully immunised compared with 94.5% in urban communities. Significant factors associated with incomplete immunisation are: children of single mothers (aOR=5.74, 95% CI 1.45 to 22.76), children delivered without skilled birth attendant present (aOR=1.93, 95% CI 1.24 to 2.99), children of mothers who did not receive postnatal care (aOR=6.53, 95% CI 4.17 to 10.22), children of mothers with poor knowledge of routine immunisation (aOR=1.76, 95% CI 1.09 to 2.87), dwelling in rural district (aOR=7.49, 95% CI 4.84 to 11.59), low-income families (aOR=1.56, 95% CI 1.17 to 2.81) and living further than 30 min from the nearest vaccination facility (aOR=2.15, 95% CI 1.31 to 3.52). Conclusions: Although the proportion of fully immunised children in Enugu state is low, it is significantly lower in rural districts. Study findings suggest the need for innovative solutions to improve geographical accessibility and reinforce the importance of reporting vaccination coverage at local district level to identify districts for more targeted interventions.